Risk assessment of adherence in hypertensives and diabetics in a sub-saharan african outpatient clinic. (2013)
Medication non adherence is a significant burden to health care utilization[1], in addition to poor disease control. But there is a paucity of structured adherence counselling as a thematic area of care. We have used a modified adherence tool for patients living with HIV and AIDs which incorporates social background, treatment preparation, adherence habits, disclosure of illness, the use of treatment partners, and assessment of potential barriers to adherence. This form was designed only to explore known characteristics that are important for adherence, but patients were asked to make judgement on their own level of adherence. Of the one hundred and eighty one eighty six (47.5%) were males while 95(52.5%) were females. The mean age was 50.83years (SD 12.54). Majority of the patients were married (81.8%) and had at least primary education. Most of the patients whom we interviewed were hypertensives (65%). One hundred and twelve (61.88%) were taking medications during a daily routine, such as eating. Most of the patients, 116(64.10%) had some knowledge about their illness and the medications they were taking by names. Majority of patients (72.4%) had disclosed their illness to their spouses. Many patients self-report that their adherence is good.